Technical Feasibility to Utilize Wasted Empty Fruit Bunch from Small Scale Farms for Simultaneous Production of Biochar and Electricity - Dwi Setiawan; Johanis Rumengan Pangala; Abdul Baits Dehana Padma Swastika; Armansyah Halomoan Tambunan (Indonesian Oil Palm Society /IOPS (Masyarakat Perkelapa-sawitan Indonesia /MAKSI), 2020)
Biochar production by pyrolysis stove and utilization of the excess heat to generate electricity, simultaneously, could improve the performance of the whole system, and give a significant solution to both energy and environmental problems. This is especially if implemented as a stand-alone facility and applied in a remote area. The purpose of this study is to evaluate technical feasibility and strategy in using pyrolysis stoves to produce biochar and generate electricity by ORC, simultaneously. This study combines various data obtained previously, which consists of pyrolysis stove design and performance test for simultaneous biochar production and thermal energy use, and ORC experiments for electricity generation. Those data then was used to analyze the technical feasibility of the simultaneous production of biochar and electricity generation using the excess heat from the pyrolysis stove. The integration of the pyrolysis stove with the ORC was conducted in a simulative study. The results showed that biochar produced using the pyrolysis stove has characteristics that are very supportive for use as a soil enhancer. Excess heat from the pyrolysis stove during the production of biochar can be used to fuel the ORC system to generate electricity. The optimum biochar yield and thermal efficiency of the ORC were found to be optimum at the stove's airflow rate of 0.034-0.035 kg/s. Accordingly, a combination of biochar production and electricity generation using the ORC system is considered to be technologically feasible to meet the sustainability requirement.